The road to reform Budget and management reforms under the Duterte administration 2016-2022.
This book chronicles the reform journey and key milestones of the Department of Budget and Management (DBM) under the Administration of President Duterte, showing how the DBM steered public expenditure management towards inclusive growth and better public service delivery.